Influence Of The Settleability Parameters For Palm Oil Mill Effluent (Pome) Pretreatment By Using Moringa Oleifera Seeds As An Environmental Friendly Coagulant. - Othman, Zalina; Bhatia, Subhash; Ahmad, Abdul Latif (2008)
Palm Oil Mill Effluent (POME) treatment is an important issue for the minimization of pollution. POME is a highly polluting effluent containing various forms of organics and inorganic suspended solids.